Complications after Nonoperative Management of Hamate Fractures. Issue 5 (24th May 2022) - Ta, Canhnghi N.; Finley, Zachary; Medvedev, Gleb A.
Abstract : Background: Hamate fractures are an infrequent injury and are often missed or have a delayed diagnosis with potential for significant patient morbidity. There is a relative paucity in the literature involving large population studies of hamate fractures and subsequent complications. Gaining a better understanding of complications associated with nonoperative management will help guide the decision for operative intervention. Methods: The PearlDiver patient records database was used to query for patients who sustained a hamate fracture using ICD-9 and ICD-10 codes. Postinjury complications within 1 year of diagnosis were assessed using ICD-9 and ICD-10 codes for diagnoses of complications. Results: A total of 1120 patients who sustained a hamate hook or body fracture met inclusion and exclusion criteria and were included in the study. Patients who were managed nonoperatively showed a nonunion rate of 2%, ulnar neuropathy rate of 1.7%, and tendon rupture rate of 0.2%. In a subanalysis using only ICD-10 codes to distinguish between hook and body fractures, hook fractures demonstrated a nonunion rate of 2.2%, ulnar neuropathy rate of 2.7%, and tendon rupture rate of 0%, while body fractures had a nonunion rate of 1.2%, ulnar neuropathy rate of 1%, and tendon rupture rate of 0%. Conclusion: The current study shows very low rates of nonunion, ulnar neuropathy and tendon rupture after nonoperative management of hamate fractures.